1991
DOI: 10.2172/6039901
|View full text |Cite
|
Sign up to set email alerts
|

Reclamation report, Basalt Waste Isolation Project, boreholes 1990

Abstract: In 1968, a program was started to assess the feasibility of storing Hanford Sitedefense waste in deep caverns constructed in basalt. This progrmu was expanded in 1976 to include investigations of the Hanford Site as a potential location for a mined commercial nuclearwaste repository. Some 98 boreholes were drilled, deepened, or modified to study the geology and hydrologyof the Hanford basalts. These boreholes were sited,on 71 drill pads ranging in size.from 0.1 to over 2.6 ha. Reclamation of these sites was be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
1993
1993

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Approximately 58% of all borehole reclamation sites were found to be well below their respective reclamation objectives, with 25% of sites devoid of grass or shrub growth. Analyses indicated that the primary causes of failure were the lack of winter rains during 1989-1990, exposure to drying winds, grazing by blacktailed jackrabbits (Lepus californicus) on shrubs, and residual herbicide activity on some sites (Brandt et al 1991a).…”
Section: _summarymentioning
confidence: 99%
“…Approximately 58% of all borehole reclamation sites were found to be well below their respective reclamation objectives, with 25% of sites devoid of grass or shrub growth. Analyses indicated that the primary causes of failure were the lack of winter rains during 1989-1990, exposure to drying winds, grazing by blacktailed jackrabbits (Lepus californicus) on shrubs, and residual herbicide activity on some sites (Brandt et al 1991a).…”
Section: _summarymentioning
confidence: 99%
“…Reintroducing native species to disturbed areas of the Hanford Site has proven difficult (Brandt et al 1992). Competition from alien weeds such as cheatgrass and Russian thistle (Salsolakalt) may play a role in limiting revegetation with native species; however, other potentially significant factors affecting revegetation success at least over the short term include soil physical properties, moisture availability, and extreme winter temperatures (Brandt et al 1990(Brandt et al , 1991(Brandt et al , 1992.…”
Section: Introductionmentioning
confidence: 99%